2017
DOI: 10.1088/1748-3190/aa7f16
|View full text |Cite
|
Sign up to set email alerts
|

Artificial insect wings with biomimetic wing morphology and mechanical properties

Abstract: The pursuit of a high lift force for insect-scale flapping-wing micro aerial vehicles (FMAVs) requires that their artificial wings possess biomimetic wing features which are close to those of their natural counterpart. In this work, we present both fabrication and testing methods for artificial insect wings with biomimetic wing morphology and mechanical properties. The artificial cicada (Hyalessa maculaticollis) wing is fabricated through a high precision laser cutting technique and a bonding process of multil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…Liu et al produced an artificial cicada wing with biomimetic properties based on geometric and structural data including vein thickness, wing mass, and flexural stiffness profile. 22 DeLe on and Palazotto developed an artificial hawkmoth wing with similar mass, geometry and natural frequencies to its biological counterpart. 23 They compared the deformation of the artificial and real wings under large flapping conditions, and while they observed some similarities in the two responses, they found that the engineered wing deformed significantly more.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al produced an artificial cicada wing with biomimetic properties based on geometric and structural data including vein thickness, wing mass, and flexural stiffness profile. 22 DeLe on and Palazotto developed an artificial hawkmoth wing with similar mass, geometry and natural frequencies to its biological counterpart. 23 They compared the deformation of the artificial and real wings under large flapping conditions, and while they observed some similarities in the two responses, they found that the engineered wing deformed significantly more.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial wings must have biomimetic wing features similar to their natural counterparts to have substantial lift force. The artificial wing’s mechanical characteristics rely heavily on venation thickness, retaining a fully stringent arrangement during flapping motion and helping to generate appropriate thrust [ 23 , 24 ].…”
Section: Wing Beat Frequency and Stroke Amplitudementioning
confidence: 99%
“…However, this is increased substantially above 5% until a visually evident fracture occurs on the wing surface, indicating its maximum deformation rate. Interestingly, the prototypes developed in this study offer much larger range of plastic deformation in contrast to the brittle CF-based peer models from the literature [53], i.e. our proposed artificial wings resist immediate fracture upon yielding.…”
Section: Mechanical Properties Testingmentioning
confidence: 99%